Survey data on swedes perception of cybersecurity information - Kävrestad, Joakim (Jönköping University, 2026)
Survey data from a survey about Swedes' preferences with regards to cybersecurity information. The set contains data from 2,149 respondents who were recruited from web panels using stratified sampling.

Data från en enkät om svenskars preferenser vad gäller cybersäkerhetsinformation. Innehåller data från 2149 respondenter som rekryterats via webbpaneler med statifierat urval baserat på ålder och kön.
Enkätdata om svenskars uppfattning om cybersäkerhetsinformation
Keywords: KNOWLEDGE (AWARENESS); MEDVETENHET; CYBERSECURITY; CYBERSÄKERHET; Computer Sciences; Datavetenskap (datalogi)